Female economic activity in Rural Malawi - Hyder, Asma (J Dev Leadersh, 2014)
This study investigates economic activities and their determinants for women in households of rural Malawi, one of the poorest countries in Sub-Saharan Africa (SSA). Three waves of household panel data for years 2006, 2008 and 2010 from the Malawi Longitudinal Study of Families and Health (MLSFH) are used to examine female labor market participation. This study includes certain important characteristics of Malawian households i.e., polygamy, ethnicity, religion and self reported health status. The study reports five different labor market outcomes for women's participation i.e., agriculture related work, market & sales activities, cottage industry, other economic activities and out of the labor market. The study finds significant relationships between these five different labor market outcomes and age cohorts, ethnicity and marriage (monogamous or polygamous).